A Way Forward for Islamic Astronomy in Malaysia - Mohd Nawawi, Mohd Saiful Anwar; Faid, Muhamad Syazwan; Dagtekin, Esma (Kajian Malaysia, 2026)
Islamic astronomy in Malaysia has developed into a well-organised discipline, supported by an ecosystem of universities, governmental institutions, observatories, and community organisations. However, Malaysia’s potential to become a better player in Islamic astronomy on the global stage could be improved. This study examines the contemporary state of Islamic astronomy in Malaysia through literature review, site visits, and a strengths, weaknesses, opportunities and threats (SWOT) analysis to assess its potential and challenges. The results indicate that Malaysia possesses numerous institutional strengths, notably contributions from universities, the federal government’s coordinating function, and the initiative-taking involvement of state mufti offices with their respective observatories. They have numerous significant achievements, including the nationwide implementation of Subh prayer and the establishment of the national crescent-sighting database and standard operating procedure (SOP). This demonstrates the nation’s capacity to convert research into practical application that usable for general public. Nevertheless, there remains room for improvement, especially in fostering stronger collaboration among academic institutions, maximising the utilisation of research facilities, and expanding international engagement and visibility. Due to this issue, this study proposes a systematic national approach that integrates universities, religious authorities, and non-governmental organisations (NGOs), drawing on insights from Türkiye and Indonesia. This article examines how Malaysia could excel in domains such as big data applications, software development, and artificial intelligence. To establish itself as a global authority in this domain, Malaysia must enhance open data practices, rejuvenate local journals, and strengthen international-local research collaborations. This study provides a framework for enhancing Islamic astronomy in Malaysia, both domestically and globally.